Análise estrutural do domínio de reconhecimento a carboidratos da lectina Dvirl de Dioclea virgata e sua correlação na indução da produção de óxido nítrico - Nóbrega, Raphael Batista da (2011)
Lectins are defined as proteins or glycoproteins of nonimmune origin that have at least one site of reversible binding to carbohydrates or glycoconjugates. Lectins of plant origin are the most studied and characterized as three-dimensional structure and biological functions related. Lectins can be found in different parts of the plant from its root to the interior of the seeds. In this last are found where the highest concentrations of lectins. Proteins considered ubiquitous in nature, different biological activities have been attributed to them. The structural study of lectins from the technique of X-ray crystallography has been the most widely used to identify the exact position of atoms arranged in the protein structure. This was the method adopted for the resolution of native and complexed structures with X-man of the DvirL lectin obtained from plant Dioclea virgata belonging to the subtribe Diocleinae, which is the most studied among the lectins of the family Leguminosae. DvirL presents multimeric structure composed of monomers with mass around 25.5 to 30.0 kDa, and their arrangement in biological tetramer is composed of dimers of dimers. The characteristic dimer-tetramer equilibrium is dependent on pH. The main one is the subunit, and from its processing are formed subunits: , and . This lectin has 237 amino acid residues and a single site for carbohydrate recognition by monomer which is stabilized by the presence of divalent ions Ca2+ and Mn2+ required for maximum affinity for its sugar ligand and their biological activities. The carbohydrate recognition domain (CRD) is formed in protein surface by a sequence of loops located above the site for ions. The degree of specificity of lectins for sugars is given by the relative positions of conserved residues present in the sugar binding site. In this study it was determined that the volume of the CRD can be used to predict the potential of a lectin for recognition of complex glycans. DvirL can bind the X-man via hydrogen bonds between the indolyl and Tyr12 and Van der Waals interactions. The ability to induce nitric oxide production by endothelial cells from different concentrations of lectins was evaluated and found to be dependent on the interaction of endothelial cells with the carbohydrate binding domain, showing DvirL be a great inducer of production nitric oxide.